Local Government and Road Infrastructure Delivery: Nigeria Experience - Ayotunde David Odewale (TheJournalish: Social and Government, 2021)
The provision of essential and basic infrastructure, especially at the Local Government level in Nigeria constitutes a major role in socio-economic and political development, and in improving the standard of living at the grassroots. Sadly, the road infrastructures are in a state of dilemma particularly the Local government roads due to so many constraints. The paper intends to look at these constraints and proffer possible solutions. Both primary and secondary methods were employed. The paper discovered that local government roads constitute the highest trunks of roads, and which got increasing day-by-day due to its proximity to the populace, and yet, the most negligible trunk of road in Nigeria. Finally, some recommendations were articulated.